Investigation of micro-crack occurrence conditions in diffusion bonded Cu-304 stainless steel couple - Yilmaz, O; Aksoy, M (Elsevier Science Sa, 2002)
Kirkendall effect has been used for calculation of intrinsic diffusion coefficients at the interface of diffusion bonded 304 stainless steel and electrolytic copper. Welding conditions have been chosen at temperatures in the range 700-900 degreesC for times of up to 30 min and pressures of up to 12 MPa. Microstructure of samples has been assessed using metallography, tensile testing, and scanning electron microscopy (SEM). Diffusion distance, and concentration distribution have been detected by using SEM and EDS analysis, Moreover, Heumann and Darken methods have been used in calculations of intrinsic and chemical diffusion coefficients. Under optimum bonding conditions, it was observed that the conditions giving the quotient (D-Cu/DFe+Cr+Ni) is different than unit propagated micro-voids at copper side in grain boundaries. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: diffusion welding; Kirkendall effect; intrinsic diffusion coefficients